Localization of FtsI (PBP3) to the Septal Ring Requires Its Membrane Anchor, the Z Ring, FtsA, FtsQ, and FtsL - Weiss, David S. (American Society for Microbiology, 1999)
Assembly of the division septum in bacteria is mediated by several proteins that localize to the division site. One of these, FtsI (also called penicillin-binding protein 3) of Escherichia coli, consists of a short cytoplasmic domain, a single membrane-spanning segment, and a large periplasmic domain that encodes a transpeptidase activity involved in synthesis of septal peptidoglycan. We have constructed a merodiploid strain with a wild-type copy of ftsI at the normal chromosomal locus and a genetic fusion of ftsI to the green fluorescent protein (gfp) at the lambda attachment site. gfp-ftsI was expressed at physiologically appropriate levels under control of a regulatable promoter. Consistent with previous results based on immunofluorescence microscopy GFP-FtsI localized to the division site during the later stages of cell growth and throughout septation. Localization of GFP-FtsI to the cell pole(s) was not observed unless the protein was overproduced about 10-fold. Membrane anchor alterations shown previously to impair division but not membrane insertion or transpeptidase activity were found to interfere with localization of GFP-FtsI to the division site. In contrast, GFP-FtsI localized well in the presence of β-lactam antibiotics that inhibit the transpeptidase activity of FtsI. Septal localization depended upon every other division protein tested (FtsZ, FtsA, FtsQ, and FtsL). We conclude that FtsI is a late recruit to the division site, and that its localization depends on an intact membrane anchor.